EAHKM+: energy-aware secure clustering scheme in wireless sensor networks. (2018) - Messai, Mohamed-Lamine; Seba, Hamida
The effective technique to save energy in wireless sensor networks (WSNs) is clustering. However, organising WSNs into clusters securely is a challenging task in regard to the vulnerabilities of these networks. In this paper, we provide a secured cluster formation by proposing a new symmetric key management scheme for hierarchical WSNs (HWSNs). The new scheme is called EAHKM+ (energy aware hierarchical key management in WSNs). Only three keys are pre-distributed in each sensor node before deployment. EAHKM+ assures the establishment of a pairwise key between each sensor node and its cluster head, thus the establishment of a broadcast key in each cluster in the network. Through comparison with other proposed key management schemes in hierarchical WSNs, we show that EAHKM+ is an energy-efficient, flexible, robust and scalable solution to the key management problem in clustered WSNs.